Evaluation of some micronutrients in patients infected with Giardia lamblia in Hawler city - bakre, Hawre Mustafa; Ahmed, Salar Adnan; Faqi, Sharmeen Qadir (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: The micro aerophilic flagellated protozoan parasite, Giardia lamblia, is the most common intestinal pathogen infecting human and a major diarrheal disease found throughout the world. It can cause acute or chronic diarrhea contributing to nutritional status, growth, and intellectual function. This prospective study evaluated the association between giardiasis and blood minerals disorders in Hawler city. Methods: The present study was carried out at the College of Medicine, Hawler Medical University, via collaborating study between the Department of Biochemistry and the Department of Microbiology. The study was carried out on 50 patients with giardiasis and 65 age and sex matched healthy controls. Examination of fecal samples for detection of Giardia cyst and/or trophozoite was carried out using the direct wet smear, while serum zinc, iron and copper levels were measured for both groups spectrophotometrically using commercial diagnostics kits. Results: The levels of serum zinc and iron in patients infected with Giardia lamblia were significantly lower (P <0.01) compared to normal healthy control, while the differences in the level of serum copper was significantly higher (P <0.01). Conclusion: : In the frame of this work we delineate that Giardia lamblia infection had a significant effect on serum trace elements reflected by, significant decrease in serum zinc and iron levels, whereas the level of copper increased too in a statistically significant manner.